Fundamentals of guided-wave optoelectronic devices - Chang, William S. C. 1931-2015 (Cambridge University Press, 2010)
Uniquely combines both the optical and electrical properties of guided-wave optoelectronic devices, providing key concepts and practical analytical techniques.